Polar body biopsy - Montag, Markus; Köster, Maria; Strowitzki, Thomas; Toth, Bettina (Fertility and sterility, 2013)
Polar body biopsy combined with array comparative genomic hybridization allows detection of maternal chromosomal aberrations. Although it has limitations, it can be seen as an alternative to blastomere and trophectoderm biopsy.